Characterisation of the fast-ion edge resonant transport layer induced by 3D perturbative fields in the ASDEX Upgrade tokamak through full orbit simulations. (27th November 2018) - Sanchis, L; Garcia-Munoz, M; Snicker, A; Ryan, D A; Zarzoso, D; Chen, L; Galdon-Quiroga, J; Nocente, M; Rivero-Rodriguez, J F; Rodriguez-Ramos, M; Suttrop, W; Van Zeeland, M A; et al.
Abstract: In recent experiments at the ASDEX Upgrade tokamak the existence of an Edge Resonant Transport Layer (ERTL) was revealed as the main transport mechanism responsible for the measured fast-ion losses in the presence of externally applied 3D fields. The Monte Carlo orbit-following code ASCOT was used to study the fast-ion transport including the plasma response calculated with MARS-F, reproducing a strong correlation of fast-ion losses with the poloidal mode spectra of the 3D fields. In this work, a description of the physics underlying the ERTL is presented by means of numerical simulations together with an analytical model and experimental measurements to validate the results. The degradation of fast-ion confinement is calculated in terms of the variation of the toroidal canonical momentum ( δP ϕ ). This analysis reveals resonant patterns at the plasma edge activated by 3D perturbations and emphasizes the relevance of nonlinear resonances. The impact of collisions and the radial electric field on the ERTL is analysed.